Employing MCNP to optimize experimental design for compressed sensing neutron source imaging - Anuar N.; Marianno C.; McClarren R.G. (Elsevier B.V., 2023)
Chlorine compounds; Imaging systems; MATLAB; Neutron sources; Neutrons; Pixels; Polyvinyl chlorides; Water tanks; Array configurations; Compressive sensing; Experimental apparatus; Least Square; Monte carlo n particles; Polyvinyl chloride pipes; Random combination; Running simulations; Compressed sensing